Acute pseudotumoral hemicerebellitis in a child: a rare and distinct entity? - Alberini, Elena; Vellante, Valerio; Zennaro, Floriana; Calligaris, Lorenzo; Barbi, Egidio; Carrozzi, Marco; Devescovi, Raffaella (J Child Neurol, 2015)
A pseudotumoral presentation of acute hemicerebellitis is rare in pediatric age. The authors report a new single case study of a 7-year-old child with pseudotumoral unilateral cerebellitis mimicking an intracranial tumor, which clinically presented itself with signs of intracranial hypertension and mild contralateral hemiparesis, completely recovered after anti-inflammatory therapy. Brain magnetic resonance imaging (MRI) was essential for the differential diagnosis between inflammatory and neoplastic processes. The literature highlighting specific clues about pseudotumoral hemicerebellitis as a distinct clinical and radiological entity is reviewed.
Keywords: Brain; Cerebellar Diseases; Child; Diagnosis, Differential; Encephalitis; Humans; Magnetic Resonance Imaging; Male

Involuntary movements after correction of vitamin B12 deficiency: a video-case report. - Zanus, Caterina; Alberini, Elena; Costa, Paola; Colonna, Franco; Zennaro, Floriana; Carrozzi, Marco (Epileptic Disord, 2012)
Involuntary movements can appear before and after initiation of vitamin B12 treatment. The pathogenesis of involuntary movements in vitamin B12 deficiency and their relationship with cobalamin injection remain unclear due to a lack of video-EEG documentation making the electroclinical correlation difficult to ascertain. Here, we report video-EEG and neuroimaging findings of an 11-month-old girl with vitamin B12 deficiency, who acutely developed involuntary movements a few days after initiation of vitamin B12 treatment with normal vitamin plasmatic levels. Abnormal movements were a combination of tremor and myoclonus involving the face, mouth, and left arm, which disappeared after discontinuation of therapy. [Published with video sequences].
Keywords: Atrophy; Brain; Dyskinesias; Electroencephalography; Female; Humans; Infant; Magnetic Resonance Imaging; Myelin Sheath; Myoclonus; Tremor; Video Recording; Vitamin B 12; Vitamin B 12 Deficiency; Vitamins